CHANGES IN PATHOMORPHOGENESIS OF THE HYPOTHALAMO-HYPOPHYSIARY SYSTEM IN CASES OF SUDDEN HEART DEATH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In the existing literature, limited studies have concurrently examined and correlated the morphofunctional parameters of the hypothalamus, pituitary gland, and adrenal glands in individuals with mood disorders, particularly in relation to cardiovascular risks. There is a scarcity of data on the morphometric correlations within the hypothalamic-pituitary-adrenal (HPA) axis structures, which holds significant interest for understanding comorbidity. Recent investigations employing morphometric techniques have primarily focused on stress-related disorders since the 2000s. A key attribute of the HPA axis is its capacity to integrate peripheral stress signals and orchestrate autonomic and neurohumoral responses. By applying morphometric approaches to study the HPA axis, objective data can be obtained for statistical evaluation. Assuming that structural integrity corresponds to functional adequacy, this research attempts to characterize HPA axis organ functions in mood disorders with cardiovascular implications via morphometry. The findings indicate that dysregulation of the HPA axis plays a pivotal role in the pathogenesis of increased cardiovascular mortality in mood disorders, necessitating consideration in therapeutic approaches.